2013
DOI: 10.1002/pbc.24639
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence of primary cutaneous malignancies in children, adolescents, and young adults: A population-based study

Abstract: Non-melanoma skin cancer is very rare in children and AYA. We have shown variation in time-trends in incidence as well as in incidence patterns by race, sex, age, and histologic type, highlighting the importance of descriptive epidemiology to better understand the characteristics of these malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 25 publications
1
16
1
2
Order By: Relevance
“…Skin carcinomas are generally less common than melanoma. 37,38 In Tunisia, skin carcinoma is exceptionally prevalent among 15-to 19-year-olds, with rates of 7.8 per million for males and 16.5 per million for females. 39 In our present series, among AYAs, the median incidence of melanoma was 3 cases per million, whereas the median incidence of skin carcinomas was 18 cases per million, and these rates increased with age.…”
Section: Discussionmentioning
confidence: 99%
“…Skin carcinomas are generally less common than melanoma. 37,38 In Tunisia, skin carcinoma is exceptionally prevalent among 15-to 19-year-olds, with rates of 7.8 per million for males and 16.5 per million for females. 39 In our present series, among AYAs, the median incidence of melanoma was 3 cases per million, whereas the median incidence of skin carcinomas was 18 cases per million, and these rates increased with age.…”
Section: Discussionmentioning
confidence: 99%
“…5 An additional study examining melanoma incidence in females aged 0-30 years over a 15-year period noted a 2.5% annual increase from 1992-2006. 6 This upward trend in melanoma incidence in young women is thought to be in part attributable to a relatively new source of UV radiation: indoor tanning equipment. 7 It has been proposed that this alarming rise in melanoma may be the result of improved screening and surveillance techniques, which would result in an expected increase in the number of diagnosed thinner tumors with minimal metastatic potential.…”
Section: Introductionmentioning
confidence: 99%
“…One longitudinal study among a broader age group of adolescent girls and young women in California showed melanoma rates increasing from the early 1990s 6. Another more recent study of melanoma trends in the USA from 1992 to 2006 in children, teenagers and young adults showed that melanoma incidence rose significantly among females up to 30 years 7. On the other hand, after a similar rapid rise in teenage melanoma rates in Sweden in the 1980s, the incidence rate fell by 26% in the 1990s 8…”
mentioning
confidence: 99%